Integrated approach to delineation of drinking water protection zones - Brenčič, Mihael (Geologija, 2009)
Protection of water resources plays an important role in providing safe and reliable drinking water for people and industry. Drinking water resource protection usually comprises active and passive measures. Passive measures, consisting of different protection zones surrounding the recharge area of the drinking water abstraction point, are the most important and most widely used measures. In the paper is illustrated how the protection of drinking water is implemented through the Water Framework Directive. Protection zones are defined based on the classification of drinking water resource types. They aredivided into two groups; groundwater and surface water bodies. All of them are further divided into subgroups; groundwater into intergranular, karstic and fissured aquifers; surface water into stagnant and flowing water bodies. For all drinking water resources three protection zones are defined: inner, middle and outer zone. The outer zone was defined as the total recharge zone of the water quantities abstracted. Inside of inner zone, abstraction point zone is defined, which is protected from unauthorized access. Protection zonesfor intergranular aquifers are determined according to the isochrones based on travel times. Karstic aquifers are protected on the basis of intervention times and the level of the recharge zone karstification. Fissuredaquifers are protected according to groundwater flow velocities; if the flow is laminar, the method of intergranular aquifers is used, otherwise the method of karstic aquifer is implemented. For surface water protection zones limitation method of distances, method of isochrones and dilution and method of intervention times are used.
Keywords: pitna voda; Slovenia; Slovenija; vodni viri; vodovarstvena območja; zaščita